Assessment of the Effect of Kinesiology Taping on Scar Treatment in Children - Justyna Pogorzelska; Agata Michalska; Anna Zmyślna (Clinics and Practice)
Background: The consequences of injuries resulting from accidents are among the most common health disorders in children. A scar forms at the site of the injury. In the treatment of scars, not all methods used in adults can be used in children. The authors attempted to assess the effectiveness of using KT kinesiology taping on scars in children. The aim of the work is to assess the effect of KT on the treatment of keloid, hypertrophic scars, and postoperative adhesions in children. Methods: The study included 30 patients aged 4 to 10 years. The subjects were divided into three groups: group G1-9 patients with keloid scars, group G2-14 with hypertrophic scars, group G3-7 with postoperative adhesions. The patients underwent kinesiology taping for 8 weeks. The analyzed parameters were determined using the VSS scale and ultrasonography. Results: The analysis of the VSS scale results in relation to the type of scars showed a significant (p < 0.001) downward trend in the measured parameters for keloid and hypertrophic scars. Analysis of ultrasound results in relation to the type of scars showed a significant (p < 0.001) downward trend in the measured parameters, comparing parameters I and II for all types of scars. Conclusions: Kinesiology taping significantly changes the following scar parameters: deformability, pigmentation, and perfusion in the case of keloid and hypertrophic scars.